Predictors and Short-Term Outcomes of Patients with Contrast Induced Nephropathy following PPCI - Sheraz, Ephraim; Shafiq ur Rehman; Raja, Tanvir Ahmad; Abair ul Haq; Husnain Yousaf (Indus Journal of Bioscience Research, 2025)
Introduction: Contrast-induced nephropathy (CIN) is one of the most frequent renal complications for patients who have received primary percutaneous coronary intervention (PPCI) for ST-elevation myocardial infarction (STEMI). CIN is associated with a longer length of hospitalization, increased in-hospital mortality and poor overall survival. It is for this reason that there is a need to establish predictors of its occurrence in order to reduce the frequency of its occurrence and improve patients’ outcomes. Objectives: The main aim of the present research was to identify factors that may cause CIN and to evaluate the immediate outcomes of this condition in patients who underwent PCI in a large Pakistani teaching hospital. Materials and Methods: The current prospective study involved 200 STEMI patients who were candidates for PPCI. Patients’ baseline demographic and clinical characteristics and their biochemical profiles were also obtained with CIN as an increase of ≥0.5 mg/dL or ≥25% increase in serum creatinine. Descriptive statistics showed the following individual variables as independent predictors of CIN. Results: CIN was present in 34% of patients. These baseline characteristics were identified as critical predictors for the development of AKI were age, diabetes, baseline renal dysfunction, and contrast volume. CIN was also linked with increased length of hospital stay and increased mortality rate in the hospital. Conclusion: Despite being a potentially preventable issue, CIN continues to be a concerning factor in patients with PPCI, and risk assessment, preventive measures and the appropriate procedural approach should be defined early.